Assessing the educational quality of laparoscopic appendectomy videos on YouTube used in surgical training - Kalyoncu Aycenk, Aybegum; Altinok, Volkan; Yalcin, Onur; Topsakal, Ceren; Aybuke Emral, Merve; Benzes, Imge (Journal of the Pakistan Medical Association, 2026)
Objective: To evaluate the educational quality of laparoscopic appendectomy videos on YouTube as a learning resource for surgeons and trainees. Method: The retrospective, cross-sectional study was conducted at the Department of Paediatric Surgery, Ordu University, Ordu, Turkiye, between March and June 2024, and comprised laparoscopic appendectomy YouTube videos uploaded between January 2010 and June 2024, assessing video origin, upload date, duration, Journal of the American Medical Association score, educational quality rating score, objective component rating score, video power index, and total video quality score. Three laparoscopically experienced surgeons and three senior paediatric surgery residents independently evaluated the videos. Data was analysed using R 4.0.5. Results: Of the 64 videos reviewed, 38(59%) originated from India. Of the 20(31.2%) videos with a video power index score >10, 15(75%) had moderate quality, 3(15%) poor and 2(10%) good. Educational quality rating score and objective component rating score showed no significant differences between the groups of senior paediatric surgery residents and laparoscopically experienced surgeons (p>0.05). However, expertise influenced total video quality score (p<0.05), with senior paediatric surgery residents and laparoscopically experienced surgeons rating 40(62%) and 27(42%) videos, respectively, as of moderate quality. Poor ratings were given to 20(31.3%) videos by senior paediatric surgery residents, and to 34(53.1%) videos by laparoscopically experienced surgeons. Good ratings were given to (4(6%) videos by senior paediatric surgery residents, and to 3(4%) videos by laparoscopically experienced surgeons. Conclusion: Most laparoscopic appendectomy videos on YouTube were found to be of moderate to poor quality, highlighting the need for curated content and expert guidance to enhance learning outcomes. Key Words: Laparoscopy, Appendectomy, Education, YouTube, Appendicitis, Surgical education.